Are We Getting Value for Money from Behavioral Interventions for Offenders? A Research Note Reviewing the Economic Evaluation Literature - Settumba, S.; Chambers, G.; Shanahan, M.; Schofield, P.; Butler, Tony (2017)
© 2017 Southern Criminal Justice Association Public expenditure on the criminal justice system represents a significant fiscal burden to government worldwide, making the economic evaluation of interventions aimed at improving justice outcomes critical to informing resource allocation. This study systematically reviews and assesses the scope and quality of economic evaluations of behavioral interventions aimed at reducing reoffending. Only seventeen studies met the inclusion criteria, with wide variation in methodological approaches, including differences in costing perspectives, study design, and the definition of cost and outcome measures. The majority of behavioral interventions for offenders remain unevaluated from an economic perspective, representing a significant evidence gap for informing cost-effective and efficient allocation decision. Based on the studies reviewed, economic benefit can be derived from investing in offender behavioral programs. However, whether this investment represents ‘value for money’ remains unclear. What is clear is that economic evaluations in the justice health sector lag behind research in other areas of public policy.